PENGARUH KOMUNIKASI ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYTAWAN (STUDI KASUS KARYAWAN NON-MEDIS RUMAH SAKIT PRIMA PEKANBARU) - Deandra, Tamara Maretsa; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the effect of organizational and environmental communication on employee job satisfaction (Case Study of Non-Medical Employees at the Prima Pekanbaru Hospital). The population in this study were non-medical employees from Prima Pekanbaru Hospital with 76 samples taken, which were calculated using the Slovin formula. The sampling method in this study is in the form of primary data and secondary data using questionnaires, interviews and documents in the company. The research method used is simple regression analysis, multiple regression analysis, simultaneous and partial determination coefficient analysis, and hypothesis testing, namely the F test and T test. Data analysis used is to use SPSS ver 25 for windows.This study proves that the research shows that organizational communication on employee job satisfaction shows a significant effect on employee job satisfaction at Prima Hospital Pekanbaru. T test results indicate that the work environment on employee job satisfaction has significance to the job satisfaction of non-medical employees at Prima Pekanbaru Hospital. F test results show that simultaneous organizational and work communication has a significant and significant effect on job satisfaction received. Keywords: Organizational communication, work environment, job satisfaction